Assistive Technology in English Learning by A Visually Impaired Student at Inclusive School - Sarah Dion Chiquita Marpaung; Rahmadsyah Rangkuti; Bahagia Tarigan (Asian TESOL Journal, 2022)
The objectives of this study were to describe factual information about the process of learning using JAWS (Job Access with Speech) and MELDICT (Mitra Netra Electronic Dictionary), to know empirical evidence about the improvement of a visually impaired student, and to analyse the student and teacher perceptions of using JAWS and MELDICT in learning English. This study was conducted by using a descriptive qualitative design. The subject of this study was a visually impaired student who studied in inclusive school SMA Negeri 2 Lubuk Pakam. The data were analysed by using the Louis Cohen technique (2018). The data on this research were the description process of using JAWS and MELDICT, Pre-test and post-test results, the transcript of the teacher interview, the transcript of the student interview, and the teachers' result of the questionnaire. The findings of the study revealed that a visually impaired student improved his English by using JAWS and MELDICT with some processes of learning, such as (i) technical preparation, (ii) listening process, (iii)cognitive process (iv)reading process (v) writing process. The research showed that JAWS and MELDICT could improve a visually impaired student's writing skill. The use of JAWS and MELDICT enhanced student's motivation in writing as the student showed active participation during the writing activities. JAWS and MELDICT empowered student's creativity since they enabled the student to explore when expressing his ideas. The improvement was significant, as shown in the written texts. The student's score in the Pre-test was 12, and it increased to 20 in the post-test